Countering The Crimes of Money Laundering and Terrorism Financing in Indonesia Digital Banking: A Legal Approach Perspectives - Ramadianto, Anang Riyan; Wicaksono, Bayu Akbar (Indonesian Journal of Counter Terrorism and National Security, 2023)
The practice of money laundering is not new nowadays. People have been transferring illegally obtained money (illegal money) to the legal system for a long time (the world of regular money). It is unlawful to possess this kind of money, thus this is done to try to prevent getting caught. Whereas acts of providing, gathering, donating, or lending money, directly or indirectly, with the intent to be used and/or which are known to be used to support terrorist activities, terrorist groups, or terrorists, are considered to be funding terrorism. During the Covid-19 pandemic, digital banking in Indonesia grew rapidly, making transactions for customers relatively simple. Thus, if the government does not make significant steps to combat terrorism financing with the many current legislation, this will become an issue. As a result, in order to stop the financing of terrorism in Indonesia, digital banks must have an AML-CFT system that includes customer due diligence and regular client evaluations. To stop these problems, a number of linked institutions have regulations.